Complete sequence and organization of the Serratia marcescens biotin operon - Sakurai, Naoki; Akatsuka, Hiroyuki; Kawai, Eri; Imai, Yuji; Komatsubara, Saburo (Microbiology (Society for General Microbiology), 1996)
Research Laboratory of Applied Biochemistry, Tanabe Seiyaku Co. Ltd, 16-89 Kashima-3-chome, Yodogawa-ku, Osaka 532, Japan ABSTRACT The nucleotide sequence of the biotin ( bio ) operon of wild-type Serratia marcescens Sr41 was determined. Five ORFs were identified to encode BioA (7,8-diaminopelargonic acid aminotransferase), BioB (biotin synthase), BioF (7-keto-8-aminopelargonic acid synthase), BioC (an enzyme catalysing the synthesis of pimeloyl-CoA) and BioD (dethiobiotin synthase), in this order. The operon was deduced to be transcribed divergently to the left into bioA and to the right into the bioBFCD genes. The promoters and a common predicted operator for both bioA and bioBFCD genes were located between the bioA and bioB genes. The predicted amino acid sequences of these enzymes were similar to the sequences of the corresponding enzymes of Escherichia coli. Analysis of expression of the lacZ structural gene fused with the bioA and bioB promoters revealed that the biotin operon was subject to biotin-mediated feedback repression. 1 Author for correspondence: Naoki Sakurai. Tel: +81 48 433 2737. Fax: +81 48 433 2734. e-mail: nsakurai@tanabe.co.jp Keywords: biotin biosynthesis, biotin operon, Serratia marcescens Present address: Lead Generation Research Laboratory at Toda, Tanabe Seiyaku Co. Ltd, 2-50, Kawagishi-2-chome, Toda-shi, Saitama 335, Japan.